Gramática histórica vasca o vasco-iberismo (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The main evidence for a genetic relationship between languages resides in the help each of these offers in order to reconstruct a common protolanguage and studying the history of the remaining languages, not in any supposed superficial similarities which cannot be formulated as regular phonetic correspondences existing between them. As regards Basque and Iberian, as well as the fact that it is impossible to decipher and understand Iberian texts through Basque, there have been no advances whatsoever —and even er- rors and regressions— to date in using Iberian material to reconstruct proto- Basque and in researching the (pre)history of Basque.We consider it vital that Bascologists, steering clear of unfounded illusions, analyse the facts on the basis of the best Basque philology and the most productive theories and methods available regarding linguistic change and reconstruction. We therefore defend the notion that research into processes of grammaticalisation has already contributed, and will continue to do so in the future, important advances in reconstructing PV, and should be consistent with previous developments such as reconstruction based on the Canonical Form or Holistic Typology.
Keywords: Basque-Iberism; Similarities; Genetic Relationship; Historical Grammar; Grammaticalisation; Reconstruction